2017
DOI: 10.1016/j.jpha.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Square wave voltammetric quantification of folic acid, uric acid and ascorbic acid in biological matrix

Abstract: Nowadays, modified electrodes with metal nanoparticles have appeared as an alternative for the electroanalysis of various compounds. In this study, gold nanoparticles (GNPs) were chosen as interesting metal nanoparticles for modifying of carbon paste electrode (CPE). GNPs and the gold nanoparticles-modified carbon paste electrode (GNPs/CPE) were characterized by UV–Vis spectroscopy, transmission electron microscopy (TEM) and scanning electron microscopy (SEM). GNPs/CPE as a simple and sensitive electrode was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Various eco-friendly working electrodes replacing commonly used hanging mercury drop and film electrodes were proposed for folic acid determination. Among them a wide range of modified [7][8][9][10][11][12][13][14][15][16][17][18][19][20], amalgam and metal film electrodes [21][22][23][24] were reported. Since 2000 when bismuth film electrodes were reported for the first time [25], bismuth has been used as an attractive and popular electrode material for determination of many inorganic and organic species [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Various eco-friendly working electrodes replacing commonly used hanging mercury drop and film electrodes were proposed for folic acid determination. Among them a wide range of modified [7][8][9][10][11][12][13][14][15][16][17][18][19][20], amalgam and metal film electrodes [21][22][23][24] were reported. Since 2000 when bismuth film electrodes were reported for the first time [25], bismuth has been used as an attractive and popular electrode material for determination of many inorganic and organic species [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…No anodic oxidation of the molecule was reported either on the second oxidation step of the CV due to the polymer that is prone to overoxidize at 0.7-0.8 V/Ag and hinders the electrochemical signal of the analyte [25,26,29,30]. The polymeric structures undergo an overoxidation process at 0.8 V/Ag and the capacitive current blocks the potential anodic peak of the analyte and no signal was detected.…”
Section: The Electrochemical Oxidation Of Famentioning
confidence: 99%
“…A well-defined anodic peak at −0.2 V/Ag was observed during the DPV analysis and was linked to the electrochemical oxidation of the polypyrrole backbone. According to studies from the literature, the electrochemical oxidation of FA to dehydrofolic acid takes place at around 0.7-0.8 V independent of the pH value [25][26][27][28], by losing two protons (H + of C( 9) and H + of N( 10)) and two electrons (Scheme 1, compound II) [22,26]. In our study, this process cannot be observed due to the capacitive current determined by the polymeric layer that blocks the signal of the anodic peak of the analyte.…”
Section: The Electrochemical Oxidation Of Famentioning
confidence: 99%
“…By plotting E p vs. ln v (the graph is not shown), the number of electrons was estimated to be n ¼ 2.14, which is in good agreement with the theoretical value stated in the literature. 12 In general, the mechanism of UA electrochemical oxidation is believed to occur via two electron and two proton transfer to form an imine of UA (Scheme 1).…”
Section: Electrode Reaction Mechanism Studymentioning
confidence: 99%
“…The electrochemical properties of such electrodes are in general strongly inuenced by non-uniform doping in diamond, boundary effects, varied ratios of graphite to diamond (sp 3 /sp 2 ), surface morphology and termination. 26,27 According to the literature survey, [9][10][11][12][13][14]21,[28][29][30][31][32][33][34][35][36][37][38] the utilization of a GCE and CPE as a working electrode is dominant in the electrochemical determination of UA. Until now, the methodology using a pencil graphite electrode (PGE) modied with over-oxidized poly(3,4-ethylenedioxythiophene) nanobers has been considered to be the most sensitive with the lowest LOD of 0.001 mM.…”
Section: Calibration Curves and Analytical Performancementioning
confidence: 99%